Effectiveness body weight strength training and plyometric in the speed and agility taekwondo athletes - Noha Zulkarnain, Alfian; Kristiyanto, Agus; Rachma, Noer (Universitas Nusantara PGRI Kediri, 2021)
From the observation of 24 athletes Taekwondo Jayabaya produced as much as 79.1% - 95.8% of athletes have the physical ability, especially the speed and agility under average value. This study aims to determine the effectiveness of exercises body weight strength training and plyometric to increase physical ability. The study used an experimental research method with a quasi-experimental type using a 2x2 factorial design. The sampling technique used purposive sampling based on inclusion criteria. The total number of samples used is 24 athletes who will be divided into 2 exercise groups. The study was conducted on the Jayabaya Taekwondo team for 6 weeks. Data collection techniques used 35 meters speed test and Illinois agility run test. Variable variance analysis using MANOVA test. In the MANOVA test, the value is obtained sig. multivariate test (0.00) and between subjects effects test of exercise on speed and agility (0.00). The results of descriptive statistics on exercises body weight strength training and plyometric on speed time (5.12)>(4.57), and agility time (19.53)> (17.64). The conclusion of this study is that body weight strength training and plyometric exercises significantly affect the physical ability of taekwondo athletes.training was Plyometric more effective in increasing the speed and agility of taekwondo athletes during the 6-week training program.